2014
DOI: 10.1021/cm503579m
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Solution-Processable n-Type Semiconductor Material Design for High-Performance Organic Field-Effect Transistors

Abstract: There have been only a limited number of reports on solution-processed n-channel organic thin-film transistor (OTFT) devices with high levels of electrical performance, because the material design process for the n-type organic semiconductors are relatively difficult compared to p-type semiconductors, and further chemical modification of the functional groups are required. As a result, the development of soluble n-type organic semiconductors with high carrier mobilities has remained a challenge. Our work addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 54 publications
1
54
0
Order By: Relevance
“…The benzobis(thiadiazole) derivative, TU-3 (Yamagata University and Ube Industries, Ltd.), [26,33] and poly(α-methylstyrene) (average M w ≈ 100 000, Sigma-Aldrich) were dissolved in 1-methylnaphthalene at a ratio of 0.045 and 0.015 wt%, respectively, and was used for the n-type semiconductor ink.…”
Section: Methodsmentioning
confidence: 99%
“…The benzobis(thiadiazole) derivative, TU-3 (Yamagata University and Ube Industries, Ltd.), [26,33] and poly(α-methylstyrene) (average M w ≈ 100 000, Sigma-Aldrich) were dissolved in 1-methylnaphthalene at a ratio of 0.045 and 0.015 wt%, respectively, and was used for the n-type semiconductor ink.…”
Section: Methodsmentioning
confidence: 99%
“…Mamada et al reported a series of BBT derivatives among which 5m has impressive atmospheric stability. 253 The mobility of 0.61 cm 2 V À1 s À1 measured inside a glove box remains unchanged for one month and performance reduction by 10% after half a year demonstrates its excellent ambient stability. A highly ambient stable fluorinated acrylonitrile derivative 5n was synthesized by Nagamatsu and co-workers.…”
mentioning
confidence: 92%
“…1,2,5 Furthermore, incorporation of the OCF 3 group into organic molecules can increase their melting point and boiling point difference under ambient pressure, and lower their surface tension, dielectric constant, and pour point. 1,11,12 These properties are particularly useful in designing electronic devices and materials; as a result, the OCF 3 -containing molecules can be found in electro-optical materials used for the development of liquid crystal displays, 13 soluble organic semiconductor, 14 and melt-processable fluoropolymers such as per-fluoroalkoxy alkanes. 12 …”
Section: Introductionmentioning
confidence: 99%